ChemInform Abstract: CH2Cl2 as Reagent in the Synthesis of Methylene‐Bridged 3, 3′‐bis(oxazolidin‐2‐one) Derivatives under Ambient Conditions. Issue 3 (January 2015) - Liu, Qingfeng; Zhang, Yansen; Zhang, Zhiguo; Liu, Tongxin; Shi, Lei; Zhang, Guisheng
Abstract Highly efficient and facile NaH‐catalyzed condensation of CH2Cl2 with cyclic carbamates to form corresponding aminal derivatives in a solvent mixture of CH2Cl2 and DMF under ambient temperature is developed.